ENHANCING SCIENCE LEARNING MOTIVATION AMONG EIGHTH-GRADE STUDENTS THROUGH PROBLEM-BASED LEARNING - Ambar Prasetyo; Syubhan Annur; Muhammad Fuad Sya’ban (Physics and Science Education Journal (PSEJ), 2025)
This study investigated the effectiveness of the Problem-Based Learning (PBL) model in improving science learning motivation among eighth-grade students at SMPN 13 Banjarmasin during the first semester of the 2023/2024 academic year. A classroom action research (CAR) design was employed, involving 25 eighth-grade students as research participants. Students’ motivation in science learning was measured using a validated questionnaire, and the data were analyzed using descriptive statistical methods. The findings revealed that the implementation of the PBL model led to a consistent improvement in students’ learning motivation across research cycles. In Cycle I, the mean motivation score reached 104.96, classified as high, with a classical mastery level of 76%. In Cycle II, the mean score increased to 121.68, falling into the very high category, while classical mastery rose to 96%. This improvement indicates that students’ engagement and motivation in science learning strengthened after iterative implementation of the PBL approach. Overall, the results suggest that the Problem-Based Learning model is effective in enhancing students’ motivation in science learning and can be considered a viable instructional strategy for improving motivational outcomes in junior high school.